Ivabradine toxicity: a case report - Kavisha Singh; Muthukumar R. Alagarraju; Carl E. Wolf; Justin L. Poklis; Nitin Kulkarni; William Tharpe; Parag H. Joshi (Journal of Medical Case Reports, 2022)
Abstract Background We describe a case of symptomatic bradycardia resulting from ivabradine toxicity by measurement of ivabradine levels, of which there are limited reports in the literature. Case presentation A 43-year-old White female presented with several days of near syncope and dizziness accompanied by a drop in her heart rate to 50 beats per minute. She was taking ivabradine for inappropriate sinus tachycardia. After excluding several other causes of bradycardia, we made the diagnosis of ivabradine toxicity by measurement of serum ivabradine levels, an approach that is currently not clinically available. Conclusions Measurement of serum ivabradine levels and knowledge of the pharmacokinetic properties of the drug can be utilized to confirm the diagnosis of ivabradine toxicity.